2005
DOI: 10.1504/ijbis.2005.007400
|View full text |Cite
|
Sign up to set email alerts
|

Situated information systems: supporting routine activity in organisations

Abstract: We argue that the traditional approach to information system design, which has become crystallised in widely promulgated Information Engineering Methodologies, is informed by a particular theory of human goal-directed action which emphasises mental representation and deliberation. This theory of action has recently been criticised for its inability to explain the fluid, unreflective, real-time action characteristic of skilled routine activity. An alternative theory stressing action as a direct response to situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…The traditional conception of how we use computing is based on a particular understanding of human action, which we have referred to elsewhere as the deliberative theory of action. 2 According to this deliberative theory of action, humans reflect on the world before acting. Traditionally computing artifacts are designed to assist us through providing a representation of the world which we can reflect on before action.…”
Section: By Vivienne Waller and Robert B Johnstonmentioning
confidence: 99%
“…The traditional conception of how we use computing is based on a particular understanding of human action, which we have referred to elsewhere as the deliberative theory of action. 2 According to this deliberative theory of action, humans reflect on the world before acting. Traditionally computing artifacts are designed to assist us through providing a representation of the world which we can reflect on before action.…”
Section: By Vivienne Waller and Robert B Johnstonmentioning
confidence: 99%
“…Managing comes down to generate and control the plan execution (i.e., acting) on the basis of sensed data to reduce the discrepancies between planned and actual actions. This stance, largely dominant in the Western culture and, so, in many research fields (Cognitive science, Artificial intelligence, Robotics, Management science,…), has inspired various computer tools to support the management of manufacturing systems, such as Material Requirement Planning or Computer Integrated Manufacturing [23], or to design information systems [25]. This is the approach which inspires a hierarchical model proposed by Martin-Clouaire and Rellier for simulating agricultural production systems [28]: a 'manager' module, standing for the farmer, decides actions to be taken according to a nominal 'plan' (given as an input), perceived events, eligibility constraints and adaptation rules; an 'operating system' allocates the necessary resources and executes the actions advocated by the manager; these actions exert their effects upon the biophysical piloted system.…”
Section: Planned Actionmentioning
confidence: 99%
“…One of the main concepts of management in the situated action paradigm is to structure the agents' environment in order to create 'affordances' (i.e., make available opportunities for fostering adapted actions; see [13,34]) and so, alleviate their cognitive burden by avoiding, as much as possible, problematic situations where they should make decisions [25]. This can be made by adapting physically and organizationally the workplace in order to transform problem-solving activities into routines.…”
Section: Issues In the Management And Coordination Of Actionsmentioning
confidence: 99%
“…In previous publications (Johnston and Milton, 2002;Johnston et al, 2005) we have identified what we call the deliberative theory of action, which assumes that an actor uses a mental model of the world to decide what to do next. We have critiqued this theory of action, arguing that in routine action, actors respond directly to structures in the environment in order to attain goals.…”
Section: Introductionmentioning
confidence: 99%
“…This paper is a conceptual output from the long term project of developing an analysis and design methodology based on the situated theory of action (Johnston and Milton 2002;Johnston et al, 2005;Milton et al, 2005). This program of research has proceeded by means of case studies.…”
Section: Introductionmentioning
confidence: 99%